Positive Solutions of a Singular Third-Order m-Point Boundary Value Problem - Shaolin Zhou; Xiaoling Han (Journal of Function Spaces and Applications)
This paper is concerned with the existence and nonexistence of positive solutions to the singular third-order m-point boundary value problem u′′′(t)+a(t)f(u(t))=0,  0<t<1,  u(0)=u'(0)=0,  u'(1)-∑i=1m-2αiu'(ξi)=λ, where ξi∈[0,1),  αi∈[0,∞)  (i=1,2,…,m-2) are constants, λ∈(0,1) is a parameter, f:[0,∞)→[0,∞) is continuous and a(·) is allowed to be singular at t=0 and t=1. The results here essentially extend and improve some known results.